2016
DOI: 10.3847/0004-637x/823/1/50
|View full text |Cite
|
Sign up to set email alerts
|

Chandra X-Ray and Hubble Space Telescope Imaging of Optically Selected Kiloparsec-Scale Binary Active Galactic Nuclei. Ii. Host Galaxy Morphology and Agn Activity*

Abstract: Binary active galactic nuclei (AGNs) provide clues to how gas-rich mergers trigger and fuel AGNs and how supermassive black hole (SMBH) pairs evolve in a gas-rich environment. While significant effort has been invested in their identification, the detailed properties of binary AGNs and their host galaxies are still poorly constrained. In a companion paper, we examined the nature of ionizing sources in the double nuclei of four kpc-scale binary AGNs with redshifts between 0.1∼0.2. Here, we present their host ga… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 136 publications
4
23
0
Order By: Relevance
“…As in Liu et al 2013 andShangguan et al 2016 we find hard X-ray emission in the nucleus displaying redder colours.…”
Section: Nuclear Activitysupporting
confidence: 76%
“…As in Liu et al 2013 andShangguan et al 2016 we find hard X-ray emission in the nucleus displaying redder colours.…”
Section: Nuclear Activitysupporting
confidence: 76%
“…Until recently, only a handful cases of dual active galactic nuclei (AGNs) -galacticscale progenitors of BSBHs -were known (Owen et al 1985;Junkkarinen et al 2001;Komossa et al 2003;Ballo et al 2004;Hudson et al 2006;Max et al 2007;Bianchi et al 2008;Guidetti et al 2008). While great strides have been made in identifying dual AGNs at kpc scales (e.g., Gerke et al 2007;Comerford et al 2009Comerford et al , 2012Comerford et al , 2015Liu et al 2010Liu et al , 2013Liu et al , 2018Green et al 2010;Fabbiano et al 2011;Fu et al 2011Fu et al , 2012Fu et al , 2015aKoss et al 2011Koss et al , 2012Koss et al , 2016Rosario et al 2011;Teng et al 2012;Woo et al 2014;Wrobel et al 2014a;McGurk et al 2015;Müller-Sánchez et al 2015;Shangguan et al 2016;Ellison et al 2017;Satyapal et al 2017), there is no confirmed BSBH at sub-pc scales (for recent reviews, see e.g., Popović 2012;Burke-Spolaor 2013;Bogdanović 2015;Komossa & Zensus 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, dual-AGN host systems may show a preference for major mergers so that enough fuel is available to power both AGNs. For example, of the threeSDSSdual-AGN systems, two are hosted by major mergers (Shangguan et al 2016). Since the sample from Treister et al (2012) extends to high redshifts and was selected based on morphology, that sample may contain a relatively higher fraction of major mergers that allow for easier visual classification, possibly accounting for the agreement between that sample and the comparison SDSS dual-AGN sample.…”
Section: Triggering Of High-luminosity Agns In Mergersmentioning
confidence: 99%